2014
DOI: 10.1186/s12245-014-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

Trauma training course: innovative teaching models and methods for training health workers in active conflict zones of Eastern Myanmar

Abstract: BackgroundMyanmar has struggled through decades of internal conflict, which has negatively impacted the country’s health outcomes. Recent government changes have brought hope and reduced conflict. The ethnic minority groups have suffered the brunt of the health consequences and reside in regions that lack health infrastructure, resources, and providers. Due to the chronic lack of healthcare providers within conflict areas, health workers (HWs) have been trained in an effort to fill the void. Research has shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…However, the trauma care systems were not fully described. The studies on the other LMICs such as Sri Lanka, Myanmar and Cambodia were focused on rehabilitation, injury surveillance, education for capacity building for trauma care rather than trauma care system contents . We could not include the countries in the study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the trauma care systems were not fully described. The studies on the other LMICs such as Sri Lanka, Myanmar and Cambodia were focused on rehabilitation, injury surveillance, education for capacity building for trauma care rather than trauma care system contents . We could not include the countries in the study.…”
Section: Discussionmentioning
confidence: 99%
“…11 Studies have shown positive impact of community health workers on NCD management in low-income and middle-income settings. [13][14][15][16][17][18] However, limited guidance exists on the specific role community health volunteers (CHVs) might play in delivering care to refugees living with NCDs in protracted displacement settings. Since 2011, the International Rescue Committee (IRC) has administered Jordan's largest CHV programme, serving both Syrian refugees in non-camp settings as well as uninsured Jordanian patients.…”
Section: Open Accessmentioning
confidence: 99%
“…23 Since 2000, several organizations have implemented the trauma training course (TTC) program with non-physician clinicians (called health workers) in Eastern Myanmar. 24 The program comprises various skills for carrying out the initial treatment of trauma, taught through simple simulations and feedback. The findings indicated that survival rates improved significantly among major trauma patients following the implementation of this program.…”
Section: Status Of Emergency Signal Functions In Myanmar Hospitalsmentioning
confidence: 99%